Education, Marriage, and Professionalization: The Modern Qatari Woman’s Dilemma - Rajakumar, Mohanalakshmi; Bengali, Mariam; Shahzad, Rumsha; Kane, Tanya (My University, 2017)
We offer observations about the obstacles to promoting a gender-inclusive labor force based on two sets of data on female Qatari students and professionals. Data set 1 is the result of a project pertaining to the disparity between education and employment among Qatari women. We surveyed 274 young women between the ages of 17 and 25 with the aim of understanding some of the reasons why Qatari women were not entering the workforce. Data set 2 derives from 350 focus groups and interviews with female students to assess the effect their tertiary education had on their marriageability. While education has delayed the age of marriage when this generation of women is compared with that of their mothers and grandmothers, the social expectations of becoming a wife and ensuing motherhood mean that marriage can restrict a woman’s working outside the home.
Keywords: arabian gulf; Frauen; gender norms; Geschlechterrolle; marriage; Normen; women; ddc:303